2014
DOI: 10.1128/jvi.01346-14
|View full text |Cite
|
Sign up to set email alerts
|

Suppressors of Cytokine Signaling 1 and 3 Are Upregulated in Brain Resident Cells in Response to Virus-Induced Inflammation of the Central Nervous System via at Least Two Distinctive Pathways

Abstract: Suppressors of cytokine signaling (SOCS) proteins are intracellular proteins that inhibit cytokine signaling in a variety of cell types. A number of viral infections have been associated with SOCS upregulation; however, not much is known about the mechanisms regulating SOCS expression during viral infection. In this study, we used two pathologically distinct intracerebral (i.c.) infection models to characterize temporal and spatial aspects of SOCS expression in the virus-infected central nervous system (CNS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
(82 reference statements)
2
14
0
Order By: Relevance
“…The SOCS (suppressors of cytokine signaling) molecules were known to negatively regulate inflammatory signaling pathways by facilitating ubiquitination and proteosomal degradation of signaling molecules [ 38 41 ]. The expression levels of SOCSs, especially SOCS1 and SOCS3, were found to be up-regulated in H3N2 and H5N1 HALo mutant infected cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The SOCS (suppressors of cytokine signaling) molecules were known to negatively regulate inflammatory signaling pathways by facilitating ubiquitination and proteosomal degradation of signaling molecules [ 38 41 ]. The expression levels of SOCSs, especially SOCS1 and SOCS3, were found to be up-regulated in H3N2 and H5N1 HALo mutant infected cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a close association between cytokine imbalance and SOCS1/3 observed in patients with a severe dengue infection suggested that the combined analysis of SOCS1/3, IL-10, and IL-6 expression levels could identify at-risk patients for severe dengue [38]. In an intracerebral infection mouse model, SOCS proteins were upregulated in brain resident cells in response to infection with yellow fever virus [39]. Moreover, Japanese encephalitis virus infection in mice led to an upregulation of SOCS1 and SOCS3 in vitro and in vivo in the mouse brain [17].…”
Section: Discussionmentioning
confidence: 99%
“…; Steffensen et al . ). We and others have shown that anti‐inflammatory agents, such as glucocorticoid, rosiglitazone, resveratrol, and GW501516, induce SOCS1 expression in macrophages and microglial cells, leading to reductions in glutamate‐mediated neurotoxicity and Aβ‐triggered inflammation (Park et al .…”
Section: Discussionmentioning
confidence: 97%